Baydawi’s Explanations for Omission İssues at Tafsir Anwar al-Tanzil wa-Asrar al-Ta’wil: Analitical Study - Yildirim, Esra (Dirasat: Shari’a and Law Sciences, 2021)
This paper aims to analytically study Baydawi’s explanations of omission issues at Tafsir Anwar Al-Tanzil wa-Asrar Al-Ta’wil. This research is an analytical study of the book "Tafsir Anwar Al-Tanzil wa-Asrar Al-Ta’wil". First, the study presents Baydawi’s concept of explanation. It then presents the clues that Baydawi uses to determine the positions of omission; and for their intended meanings. In addition, it explains the purposes of omissions mentioned by Baydawi. This study required using inductive and analytical methods by extrapolating the interpretation of Baydawi in studying the explanations of the omission issue and analyzing and criticizing its deficits. Accordingly, the researcher talked about Albaydawi, his concept of explanation, and the definition of the omission issue. Then, he analyzed the prohibitive clues at Albaydawi in the omission issues and analyzed his explanations of some of the omission issues rhetorically. The research concludes that the omission is only a grammatical necessity; Baydawi used dverbal, contextual and situational evidence to identify these omissions. He also used context and situation to identify the purposes of the omissions.